Penerapan Kombinasi Metode Entropy dan Extended Promethee II Dalam Menentukan Kepala Jurusan Pada SMK - Ahmad Zulfandi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The implementation of education in Vocational High School can not be separated from the important role of a Head of Department, especially in vocational education that becomes his area of expertise. The head of the department has many important tasks related to his field of youth. The determination of the head of the department at SMK Negeri 1 Perbaungan is carried out annually, in which the candidates are assessed in their entirety by the principal and then determined a head of the department who is fit to be the head of the department in that period. To get better results in determining the head of the department can use the Decision Support System as an application that helps the principal in determining the head of the department. A suitable method used based on this case is a combination of Entropy and Extended Promethee II methods in which it can compare between one alternative and another based on each criteria value. Weighting also uses entropy method so that the weight value generated from each alternative value can be more accurate. The resulting exprom II method presents the best candidates to be the head of the department